Finite Element Optimization Analysis of the Frame Structure of the New Steel Mold Trolley - Yang, Shuai; Liao, Xiangping; Zhi, Guoshen; Liu, Guiyang; Zou, Jiao (Manufacturing Technology Journal, 2023)
In order to test whether the design of the new steel mold trolley meets the requirements of the working conditions,the ANSYS finite element simulation and optimization analysis of the frame system of the new steel mold trolley were conducted.After the analysis, the results show that the new steel mold trolley designed basically meets the requirements of strength and stiffness, but there are some problems of insufficient strength；Through the topology optimization of the gantry frame of the new steel mold trolley frame system, the ``door shape'' section gantry structure with better force structure was obtained.The influence of the specific structural parameters of the ``door shape'' cross-section gantry structure on the overall stress of the steel mold trolley frame system was studied.The results show that the optimized steel mold trolley gantry structure has a maximum stress of 174.94MPa, an average stress of 26.22Mpa and a maximum deformation of 2.20mm under the condition of extreme load, which can better meet the actual engineering needs.
Keywords: Steel mold trolleys; Frame system; Finite element analysis; Topology optimization